2015
DOI: 10.1071/ah14152
|View full text |Cite
|
Sign up to set email alerts
|

Relinquishing or taking control? Community perspectives on barriers and opportunities in advance care planning

Abstract: Objective. This paper reports on the experiences and perspectives of community members in relation to advance healthcare directives and enduring power of attorney, including the factors that encourage or discourage engagement in advance care planning (ACP).Methods. A qualitative methodology was used involving 26 in-depth telephone interviews with community members (mean age 66 years). The aims of the interview question were to gain an understanding of: (1) motivations for engaging in ACP; (2) barriers that pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 16 publications
2
28
0
Order By: Relevance
“…This interpretation may help explain similarities in prevalence rates for both studies. Confusion about terminology for ACP and ACD was noted above and this exists in the community . Examining these two studies together suggests the importance of explaining to participants the suite of ACP and ACD documents and how they differ.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…This interpretation may help explain similarities in prevalence rates for both studies. Confusion about terminology for ACP and ACD was noted above and this exists in the community . Examining these two studies together suggests the importance of explaining to participants the suite of ACP and ACD documents and how they differ.…”
Section: Discussionmentioning
confidence: 79%
“…This is striking when compared with community prevalence rates of financial enduring powers of attorney (30%) and wills (59%). 8 Reasons advanced for this include avoiding consideration of mortality and ill-health 1,8,[17][18][19] poor public awareness of existence and utility of ACD 8,[18][19][20] and the complexity of existing legal frameworks, including variation across Australian jurisdictions. 8,19 While policy-makers and others urge people to undertake ACP, the low uptake of ACD shows challenges in Australia remain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[32][33][34][35] We support the conclusion by McLennan et al that death conversations fall within the role of health professionals, and that steps need to be taken to ensure death is not 'avoided at personal and professional levels.' 36 Increased engagement with advance care planning and end-of-life care processes that facilitate increased death conversation preparedness by GPs are currently being rolled out in New Zealand. 37 However, as the article by Cotton points out, death conversations should not be confined to the end of life.…”
Section: Discussionmentioning
confidence: 99%
“…7,24 Qualitative studies in Canada and Australia showed that inaccessibility and lack of knowledge lead to fear, avoidance and mistrust when it comes to advance care planning. 25,26 Although interventions to facilitate advance care planning continue, 9 preparation to care for loved ones as a substitute decision-maker should be synergistic and provide more cues to action, as per the Health Belief Model. 10 Three-quarters of our participants believed they would act as a substitute decision-maker in the future; the universality of this issue warrants consideration of population-based solutions.…”
Section: Openmentioning
confidence: 99%